2019
DOI: 10.1111/obr.12879
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the healthiness of packaged foods and beverages from 12 countries using the Health Star Rating nutrient profiling system, 2013–2018

Abstract: Summary We compared the healthiness of packaged foods and beverages between selected countries using the Health Star Rating (HSR) nutrient profiling system. Packaged food and beverage data collected 2013–2018 were obtained for Australia, Canada, Chile, China, India, Hong Kong, Mexico, New Zealand, Slovenia, South Africa, the UK, and USA. Each product was assigned to a food or beverage category and mean HSR was calculated overall by category and by country. Median energy density (kJ/100 g), saturated fat (g/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 24 publications
3
49
0
Order By: Relevance
“…Certain AGEs, such as CML and pyrraline, are likely to form at 120–200 °C [26,27,28]. Some studies [29,30,31,32,33] have reported that the sodium content (expressed as a percentage of mass concentration) ranges between 0.00% and 1.00% in foods, including packaged, commercially processed, and restaurant foods. Therefore, in this study, we used a temperature range of 140–180 °C and a sodium content of 0.00–1.00%.…”
Section: Methodsmentioning
confidence: 99%
“…Certain AGEs, such as CML and pyrraline, are likely to form at 120–200 °C [26,27,28]. Some studies [29,30,31,32,33] have reported that the sodium content (expressed as a percentage of mass concentration) ranges between 0.00% and 1.00% in foods, including packaged, commercially processed, and restaurant foods. Therefore, in this study, we used a temperature range of 140–180 °C and a sodium content of 0.00–1.00%.…”
Section: Methodsmentioning
confidence: 99%
“…[65][66][67][68] Moreover, recent evidence indicates that the nutrient composition of packaged food products varies importantly around the world, being considerably less healthy in LMICs such as Chile and Mexico. 69 No age group is unexposed to these dietary trends, and even infants are at risk of receiving energy-dense micronutrient-poor complementary foods. 70 Importantly, food prices have also evolved in recent years in LMICs.…”
Section: The Nutrition Environmentmentioning
confidence: 99%
“…These results can be useful to other countries that are on their way to implementing or have already implemented the use of warning labels for unhealthy packaged foods to prevent obesity, such as Peru, Uruguay, Israel, Mexico, Canada, and Brazil. A comparative study of the healthiness of packaged foods and beverages from 12 countries reported a poor HSR score for the packaged food supply in Chile in 2015 (only Hong Kong and India had poorer scores) [37], suggesting the external validity of our findings could vary from country to country.…”
Section: Plos Medicinementioning
confidence: 77%